Aggregatstabilitet, jordbearbetning och fosforförluster i ett typområde på jordbruksmark - Melakari, Anna (2005)
Large amounts of phosphorus (P) are lost from the arable land due to water erosion. Both phosphorus attached to particles and dissolved phosphorus (mainly phosphate) are transported away with drainage-water and surface runoff. Good soil structure is important in minimizing these losses.